SOCIAL CAPITAL IN KNOWLEDGE MANAGEMENT SYSTEMS FOR THE CREATIVE INDUSTRY SECTOR - Amin Khaksar (Brazilian Creative Industries Journal, 2023)
The primary aim of this scholarly article is to examine the significance of social capital within the context of knowledge management systems (KMS) in the creative industry literature. The research adopts a comprehensive approach by employing both conceptual and literature analysis and empirical quantitative and qualitative investigations for validation purposes. According to existing literature, KMS is an essential organizational process and tool for acquiring, converting, applying, and safeguarding knowledge from internal and external sources, facilitating its utilization, development, and effective management.